ROLE OF SMALL RNAs IN PLANT DEFENSE AGAINST BIOTIC AND ABIOTIC STRESSES - V. I. Malinovsky; G. B. Borovskii; E. L. Gorbyleva; I. V. Fedoseeva; E. L. Tauson; V. A. Sokolov; V. K. Voinikov (Вавиловский журнал генетики и селекции)
Small non-coding RNAs are a specific class of RNAs that regulate a variety of physiological processes in plants. Small RNAs (siRNAs and miRNAs), the pathways of formation and, particularly, their putative functions in plant defense against biotic and abiotic stresses are concisely reviewed. Techniques that enable use of this class of RNA as agents for managing plant resistance are discussed.